Evaluation of soil and water conservation practices in the north-western Ethiopian highlands using multi-criteria analysis - Teshome, Akalu; de Graaff, Jan; Stroosnijder, Leo (Frontiers in Environmental Science, 2014)
Investments by farmers in soil and water conservation (SWC) practices are influenced by the physical effectiveness, financial efficiency and social acceptability of these practices. The objective of this study is to evaluate different SWC practices in the north-western highlands of Ethiopia using various qualitative criteria and weightings based on ecological, economic and social impacts using Multi-Criteria Analysis (MCA). The study reveals that MCA is a useful evaluation tool that takes into account non-monetary and less quantifiable effects of SWC practices. Farmers employ a range of criteria to evaluate the performance of SWC practices. The relative importance of each criterion in their selection of SWC alternatives depends mostly on slope categories. In steeply sloping areas, farmers assigned the highest score for criteria related to ecological impacts; whilst preferring practices with stronger positive economic impacts in moderate and gentle sloping areas. Policy makers and development practitioners are encouraged to pay greater attention to both farmer preferences and slope specific circumstances when designing SWC strategies and programmes.